The Effect of the Implementation of the Principles of Good Governance, Government Internal Control System, and Work Discipline on the Budget Performance of the Gorontalo City Local Government (Case Study on the Regional Apparatus Organization (OPD) of Gorontalo City) - Rahmi R. Adam; Rio Monoarfa; Amir Lukum (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the influence of the application of good governance principles, the government's internal control system, and work discipline on the budget performance of the local government of Gorontalo City on the Regional Apparatus Organization (OPD). The research method used is a quantitative approach with primary data obtained through a questionnaire using a Likert scale of 1–5. The number of residents in this study is all employees of the Gorontalo City OPD. The sample used in this study was an employee of the Gorontalo City OPD, with a sampling technique using purposive sampling. The number of samples in this study was 105 respondents. Data analysis was carried out using the Multiple Linear Regression method with the help of the AMOS 24 application. The results of the study show that the principles of good governance and work discipline have an effect on the budget performance of the local government of Gorontalo City, while the government's internal control system has no effect on budget performance.